Pharmacological inhibition of LIM kinase stabilizes microtubules and inhibits neoplastic growth. - Prudent, R; Vassal-Stermann, E; Nguyen, C; Pillet, C; Martinez, A; Prunier, C; Barette, C; Soleilhac, E; Filhol, O; Beghin, A; Valdameri, G; Honoré, S; et al. (2012)
The emergence of tumor resistance to conventional microtubule-targeting drugs restricts their clinical use. Using a cell-based assay that recognizes microtubule polymerization status to screen for chemicals that interact with regulators of microtubule dynamics, we identified Pyr1, a cell permeable inhibitor of LIM kinase, which is the enzyme that phosphorylates and inactivates the actin-depolymerizing factor cofilin. Pyr1 reversibly stabilized microtubules, blocked actin microfilament dynamics, inhibited cell motility in vitro and showed anticancer properties in vivo, in the absence of major side effects. Pyr1 inhibition of LIM kinase caused a microtubule-stabilizing effect, which was independent of any direct effects on the actin cytoskeleton. In addition, Pyr1 retained its activity in multidrug-resistant cancer cells that were resistant to conventional microtubule-targeting agents. Our findings suggest that LIM kinase functions as a signaling node that controls both actin and microtubule dynamics. LIM kinase may therefore represent a targetable enzyme for cancer treatment.